AYLANMA ISITISH TIZIMLARIDA KORROZIYADAN HIMOYA QILISHDA INGIBITORLAR SINTEZ QILISH VA ULARNING TAHLILI - Shomuradov , Ulug’bek; Beknazarov , Hasan (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
A corrosion inhibitor containing nitrogen and phosphorus, water-soluble products, was synthesized, the reaction yield and test results were studied. The IR spectrum of the corrosion inhibitor PF-7.3 was analyzed.